The influence of weather conditions, predecessors and fertilizers on the yield of brewer’s barley varieties - Шкурко, В. С. (Scientific Progress & Innovations, 2012)
During the four-year study it has been established that conditions of growing years have the greatest influence on the yield of brewer's barley. Fertilizers are the most important controlled factors. Provision of barley plants with fertilizers N30P30K30 leads to the sigficant yieldincrease, regardless of its predecessor. Varieties properties also have a significant impact. A significant interaction between predecessors and varieties characteristics, predecessors and fertilizers, varieties and fertilizers, the magnitude of the influence depends on growing conditions has been established. The use of fertilizer can increase yields of barley by 0.89–1.06 t/ha, and the use of fertilizers Nutrivant Plus brewer’s barley results in slightly lower yield (0.58–0.61 t/ha).Proper selection of varieties even further can bring 0.26–0.37 t/ha.